Діяльність польських комітетів опіки в Галичині періоду Другої світової війни - Мосорко, Мар’яна Іванівна; Mosorko, Maryana Y. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті здійснено аналіз умов матеріально-побутового життя польського населення Галичини в 1941–1944 рр. Прослідковується вплив німецької окупаційної політики на зміни економічного та соціального характеру. Особливу увагу звернено на діяльність Польського комітету опіки, його роботу у сфері охорони здоров’я та соціального забезпечення. The article analyzes the conditions of material and everyday life of the Polish population of Galicia during 1941–1944. The influence of German occupation policy on changes in economic and social life is determined. Black market operations and the introduction of card system contributed to the increase in the deficit and hunger. In such circumstances, the improvement of material and everyday life of the Polish people of Galicia took up the newly created units of the Main Burns – Polish committees. Their work was aimed at establishing of orphanages, open field kitchens and food items for children and infants, providing material and medical care and so on.
Polish Social Care of Galicia During the Second World War
Keywords: Polish; Galicia; German occupation system; Polish committees; material and everyday life; поляки; Галичина; нацистський окупаційний режим; польські комітети; матеріально-побутове життя